2021
DOI: 10.11591/ijphs.v10i3.20916
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency associated with diabetic retinopathy in type 2 diabetes mellitus: A meta-analysis

Abstract: Diabetic retinopathy (DR) is the major cause of visual impairment in the working-age population with type 2 diabetes mellitus (T2DM). Magnesium (Mg) is involved in various metabolic processes and in experimental animal studies; Mg has shown essential roles in physiological eye function. Magnesium deficiency is common in T2DM; therefore we analyzed the association between serum Mg status and the presence of DR in T2DM patients. Systematic literature searching in several databases, from 1988 to September 2020, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Prospective cohort studies, retrospective cohort studies, case–control studies, and 1 meta-analysis, have shown that serum Mg 2+ is inversely associated with the risk to develop diabetic retinopathy (DR), diabetic nephropathy, diabetic neuropathy (DN), and diabetic foot complications ( 8 , 154- 156 ) ( Table 1 ). Only a few cross-sectional and case–control studies result in nonsignificant outcomes, regarding DR, DN, and macroangiopathy ( 1 , 149 ), suggesting the need for prospective study designs for future research.…”
Section: Hypomagnesemia and Cardiovascular Riskmentioning
confidence: 99%
“…Prospective cohort studies, retrospective cohort studies, case–control studies, and 1 meta-analysis, have shown that serum Mg 2+ is inversely associated with the risk to develop diabetic retinopathy (DR), diabetic nephropathy, diabetic neuropathy (DN), and diabetic foot complications ( 8 , 154- 156 ) ( Table 1 ). Only a few cross-sectional and case–control studies result in nonsignificant outcomes, regarding DR, DN, and macroangiopathy ( 1 , 149 ), suggesting the need for prospective study designs for future research.…”
Section: Hypomagnesemia and Cardiovascular Riskmentioning
confidence: 99%